2019
DOI: 10.1002/fut.22012
|View full text |Cite
|
Sign up to set email alerts
|

Volatility index and the return–volatility relation: Intraday evidence from Chinese options market

Abstract: We use unique intraday data to investigate the validity of the Shanghai Stock Exchange's the revised Chinese implied volatility index (iVX). We find that iVX is an effective barometer for the underlying exchange‐traded fund (ETF) market and can be used as a valid “fear index” when there is anxiety over large drops. Furthermore, we use robust quantile regressions and document the asymmetric relation between returns and iVX changes. We also show that behavioral theories offer better explanations for this asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(37 reference statements)
2
7
0
1
Order By: Relevance
“…Therefore, iVX can simultaneously represent the investors' sentiment in theory. Li et al (2019) find that iVX is negatively associated with the price and return of Shanghai 50ETF separately, which indirectly proves that iVX could reflect investors' panic sentiment, but did not directly measure the sentiment. Regarding the sentiment representation of the VIX created by CBOE, most of the researches take it as the known facts and conduct research on this basis ( Pan, 2018 ; Smales, 2017 ; Yang, Jhang, & Chang, 2016 ).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, iVX can simultaneously represent the investors' sentiment in theory. Li et al (2019) find that iVX is negatively associated with the price and return of Shanghai 50ETF separately, which indirectly proves that iVX could reflect investors' panic sentiment, but did not directly measure the sentiment. Regarding the sentiment representation of the VIX created by CBOE, most of the researches take it as the known facts and conduct research on this basis ( Pan, 2018 ; Smales, 2017 ; Yang, Jhang, & Chang, 2016 ).…”
Section: Introductionmentioning
confidence: 79%
“…Due to the late release of the Chinese volatility index iVX, there are few studies on iVX. The related researches mainly focus on three aspects: the prediction ability of iVX ( Qiao, Teng, Li, et al, 2019 ), the relationship between iVX and the yield, including the “leverage effect” ( Li, Yu, Luo, et al, 2019 ; Yue, Ruan, Gehricke, & Zhang, 2019 ), and the inclusion of volatility index as an indicator in the sentiment index construction system ( Xu & Zhou, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zheng et al (2017) found that the daily iVIX was positively related to the 50ETF for the period from February 9, 2015 to January 21, 2016. They claimed that in China, the iVIX should be referred to as a “greed index” rather than a “fear index.” Other authors, such as Li et al (2019), argued that although the iVIX was positively related to the 50ETF for the period from February 9, 2015 to February 13, 2018, it was negatively related to the 50ETF during the largest fluctuations and showed a strong negative comovement with the 50ETF, especially the negative returns of the 50ETF. They claimed that the iVIX is a valid “fear index.” Similarly, our results indicate that Type I jumps have a strong negative correlation, especially the negative jumps of the 50ETF.…”
Section: Empirical Analysismentioning
confidence: 94%
“…The negative correlation of the movements in the iVIX with the 50ETF is the most famous and important property of the iVIX, and this is the reason why it is called a “fear index” (e.g., Li et al, 2019). This viewpoint has been widely used for portfolio hedging and explains the popularity of the iVIX derivative.…”
Section: Empirical Analysismentioning
confidence: 99%
See 1 more Smart Citation